2012
DOI: 10.1016/j.cellsig.2011.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic acid increases soluble ST2 expression in mouse lung and human bronchial epithelial cells

Abstract: Lysophosphatidic acid (LPA), a naturally occurring bioactive lysophospholipid increases the expression of both pro-inflammatory and anti-inflammatory mediators in airway epithelial cells. sST2 Soluble ST2 (sST2), an anti-inflammatory mediator, has been known to function as a decoy receptor of interleukin (IL)-33 and attenuate endotoxin-induced inflammatory responses. Here, we show that. LPA increased sST2 mRNA expression and protein release in a dose and time dependent manner in human bronchial epithelial cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…These results may be reconciled with our findings by considering that ST2 promoter usage appears to be highly cell-type dependent and that fibroblasts may not be the major source of circulating sST2. Human endothelial cells, immune cells, and lung epithelial cells are known to express high levels of sST2 and might be the major source of circulating sST2 (40,44). We found that IL1RL1 intracellular variants associated with higher sST2 concentrations on a population level were also associated with higher sST2 protein levels in KU812 human basophils as well as in A549, U937, and Jurkat T cells.…”
Section: Discussionsupporting
confidence: 48%
“…These results may be reconciled with our findings by considering that ST2 promoter usage appears to be highly cell-type dependent and that fibroblasts may not be the major source of circulating sST2. Human endothelial cells, immune cells, and lung epithelial cells are known to express high levels of sST2 and might be the major source of circulating sST2 (40,44). We found that IL1RL1 intracellular variants associated with higher sST2 concentrations on a population level were also associated with higher sST2 protein levels in KU812 human basophils as well as in A549, U937, and Jurkat T cells.…”
Section: Discussionsupporting
confidence: 48%
“…7, D and E). We have shown that LPS treatment reduces lung epithelial integrity (40,41). Here, we showed that LPS increased dextran leak in MLE12 cells (Fig.…”
Section: Erk Regulates Cortactin Ubiquitination and Degradation-mentioning
confidence: 63%
“…We have shown that LPS potently induces cytokine release (39) and epithelial barrier disruption (40,41). LPS treatment also induced cortactin degradation in a time- (Fig.…”
Section: Lps Induces Cortactin Degradation In Lung Epithelial Cells Amentioning
confidence: 99%
“…ST2L is a classic type I membrane receptor, containing three extracellular IgG-like domains, a transmembrane domain, and an intracellular Toll/IL-1 receptor (TIR) domain (18). We have demonstrated that lysophosphatidic acid regulates sST2 gene expression in human lung epithelia (19). Recently, we also showed that ST2L is ubiquitinated and degraded in response to IL-33 (5).…”
Section: Introductionmentioning
confidence: 99%